Estimations of angles between some axes in radio pulsars from catalog at 1000 MHz - Nikitina, E.B.; Malov, I.F. (Advances in Astronomy and Space Physics, 2011)
There are some known theoretical models used for investigations of pulsars at present. One of the most important parameters for the check of existing pulsar models is the angle β between an axis of an emission cone (a direction of a magnetic moment vector) and a pulsar rotation axis. Some results of calculations of this angle are presented. For such calculations the sample of pulsars from the paper of Van Ommen, Alessandro et al. (1997) was used. The estimations of the angle β was carried out in three ways. The first two ways are based on some statistical relationships. The third way uses observable values of positional angles and shapes of average profiles for individual pulsars only. The distributions of angles β obtained by three methods and some results of their comparison are discussed.